Immune Mechanisms in Medium and Large Vessel Vasculitis - Weyand, Cornelia M. (Nat Rev Rheumatol, 2013)
Vasculitis of the medium and large arteries, most often presenting as giant cell arteritis (GCA), is an infrequent, but potentially fatal type of immune-mediated vascular disease. The site of the aberrant immune reaction, the mural layers of the artery, is strictly defined by vascular dendritic cells, endothelial cells, vascular smooth muscle cells and fibroblasts which engage in an interaction with T cells and macrophages to ultimately cause luminal stenosis or aneurysmal wall damage of the vessel. A multitude of effector cytokines, all known as critical mediators in host-protective immunity, has been identified in the vasculitic lesions. Two dominant cytokine clusters, one centering on the IL-6/IL-17 axis, the other on the IL-12/IFN-γ axis, have been connected with disease activity. These two clusters appear to serve different roles in the vasculitic process. The IL-6/IL-17 cluster is highly responsive to standard corticosteroid therapy, whereas the IL-12/IFN-γ cluster is resistant to steroid-mediated immunosuppression. The information exchange between vascular and immune cells and stabilization of the vasculitic process involves members of the NOTCH receptor and ligand family. Focusing on elements in the tissue context of GCA, instead of broadly suppressing host immunity, may allow for a more tailored therapeutic approach and spare patients the unwanted side-effects of aggressive immunosuppression.